Fidelity to territory and mate and the causes and consequences of breeding dispersal in American goshawk (Astur atricapillus). - Richard T Reynolds; Shannon L Kay; Jeffrey S Lambert; Martha Ellis (PLoS ONE)
Using mark-resight data, we investigated fidelity to territory and mate as well as breeding dispersal rates and the causes and consequences of breeding dispersal in a 20-year study of American goshawks (Astur atricapillus) in Arizona, USA. Generalized Additive Mixed Models were used to identify the relative contributions of four prominent explanatory variables (eggs laid, nest failed, nest successful, mate loss) and 21 individual and environmental variables in a machine learning Conditional Inference Forest to predict breeding dispersal. Ninety-five percent of males and 92% of females exhibited lifetime territory fidelity and 97% exhibited lifetime mate fidelity. Mate loss alone (to divorce, possible emigration or death) made the biggest difference in the predicted probability of dispersal (0.11 with mate loss, 0.005 with mate retention). Yet, in 80% of mate losses a hawk stayed on its territory to eventually nest with a new mate. Territory fidelity was highest when the mate was retained in the next breeding and the pair's previous attempt produced fledglings. All males and 86% of females that dispersed to a territory in our study area moved no farther than to a 3rd-order neighboring territory (crossed 2 territories). Despite equivocal evidence of dispersal to territories more frequently occupied by egg-layers, there was otherwise little evidence that hawks on average dispersed to better territories. On average reproduction did not improve post-dispersal and dispersers did not move to territories with greater total (all monitored yrs) reproduction. Goshawks losing their mates appeared to use a home-based mate searching that minimized loss of a familiar territory by waiting on their territory for a new mate and prospecting nearby territories for unpaired mates. The small sample of nearby prospected territories, combined with fortuitous occurrences of unpaired mates, resulted in random (with respect to quality) selections of territories by dispersers.